Philippine Irrigation Development: Overview, Determinants, and Policy Issues - Cristina C. David (Philippine Institute for Development Studies (PIDS), 1995)
Irrigation is a key element for increasing food productivity and self-sufficiency. In the light of severe fiscal problem, underdeveloped communication system, energy crisis and dismal market infrastructure, public expenditures and support for irrigation system have significantly declined. This paper analyzes the policy issues in irrigation development by adopting an integrated framework suggested by Roumasset. Policy design regarding project selection, design and construction, operation, maintenance, cost recovery and administration are examined.
Keywords: 330; infrastructure; capital investment